2015
DOI: 10.3390/molecules200712266
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Evaluation of New Podophyllotoxin Derivatives with in Vitro Anticancer Activity

Abstract: A series of novel podophyllotoxin derivatives were designed and synthesized. The cytotoxic activities of these compounds were tested against three tumor cell lines (HeLa, K562, and K562/A02). Most of the derivatives (IC50 = 1-20 μM) were found to have stronger cell growth inhibitory activity than positive control etoposide. Among them, 4β-N-[(E)-(5-((4-(4-nitrophenyl)-piperazin-1-yl)methyl)furan-2-yl)prop-2-en-1-amine]-4-desoxy-podophyllotoxin (9l) demonstrated significant inhibitory activity against HeLa, K56… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Podophyllotoxin (PT) has been used as an herbal drug in traditional folk remedies for preventive and therapeutic applications for more than 1000 years. PT, one of the active cyclolignan compounds extracted from Podophyllum peltatum and P. hexandrum, has been reported to provide beneficial effects in patients with intestinal Ascaris lumbicoides-induced symptoms, venereal warts, lymphoma, and cancers [7,8]. Compelling reports have demonstrated that PT-derived anticancer drugs play a powerful role in inhibiting topoisomerase II activity and inducing apoptosis of several types of cancers, including female-related tumors, non-Hodgkin's lymphomas, and lung cancers [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Podophyllotoxin (PT) has been used as an herbal drug in traditional folk remedies for preventive and therapeutic applications for more than 1000 years. PT, one of the active cyclolignan compounds extracted from Podophyllum peltatum and P. hexandrum, has been reported to provide beneficial effects in patients with intestinal Ascaris lumbicoides-induced symptoms, venereal warts, lymphoma, and cancers [7,8]. Compelling reports have demonstrated that PT-derived anticancer drugs play a powerful role in inhibiting topoisomerase II activity and inducing apoptosis of several types of cancers, including female-related tumors, non-Hodgkin's lymphomas, and lung cancers [4,8,9].…”
Section: Introductionmentioning
confidence: 99%
“…The cyclohexane core generally has enriched the medicinal chemistry armamentarium with several bioactive candidates having diverse biological activities such as antipsychotic 5 , expectorant 6 , anticonvulsant 7,8 , analgesic 9 and anticancer activities [10][11][12] . Etoposide (I) and Teniposide (II) contain cyclohexane moiety in their structures and are used in cancer chemotherapy for the treatment of lung cancer, acute leukemia and lymphoma through a cytotoxic mechanism of DNA-topoisomerase II inhibition [13][14][15] . Moreover, the aminoacyl pharmacophore chain and amide moiety were included in the structural frame of different antitumor compounds, III and IV (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…However, its therapeutic use has been restricted due to its high toxicity . Extensive efforts to reduce its toxic effects led to the development of its semisynthetic derivatives etoposide and teniposide, which are currently used in combination cancer chemotherapy but have different mechanisms of action than podophyllotoxin. , Reports on completely synthetic analogues of podophyllotoxins are rather limited due to its highly complex structure. Recently, there has been a growing interest in the development of aza analogues of A that retain key structural aspects and can be synthesized in a single-step, one-pot multicomponent reaction .…”
mentioning
confidence: 99%